2019
DOI: 10.1101/512459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinome-wide activity classification of small molecules by deep learning

Abstract: Deep learning is a machine learning technique that attempts to model high-level abstractions in data by utilizing a graph composed of multiple processing layers that experience various linear and non-linear transformations. This technique has been shown to perform well for applications in drug discovery, utilizing structural features of small molecules to predict activity. However, the application of deep learning to discriminating features of kinase inhibitors has not been well explored. Small molecule kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Ligand-based deep learning approaches have also been of benefit. In one such model, Allen et al created a multi-task deep neural network (MTDNN) models to predict kinase activity of small molecules across the human kinome (31). Briefly, comprehensive kinase bioactivity data was obtained from ChEMBL and the commercial database Kinase Knowledgebase KKB (32).…”
Section: Ligand-based Cheminformatics Modeling Using Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligand-based deep learning approaches have also been of benefit. In one such model, Allen et al created a multi-task deep neural network (MTDNN) models to predict kinase activity of small molecules across the human kinome (31). Briefly, comprehensive kinase bioactivity data was obtained from ChEMBL and the commercial database Kinase Knowledgebase KKB (32).…”
Section: Ligand-based Cheminformatics Modeling Using Machine Learningmentioning
confidence: 99%
“…In general, more data incorporated into the training set generally results in better model performance (less overfitting), especially for deep neural networks. For example, Allen et al found that for predicting drug-kinase activity using deep learning, model performance was significantly less when the number of active compounds for a kinase was less than 500 and further degraded when there was less than 50 (31). This is with respect to single-task learning (i.e.…”
Section: Repurposingmentioning
confidence: 99%